Dedifferentiated liposarcomas treated with immune checkpoint blockade: the MD Anderson experience - Torres, Madeline B.; Leung, Cheuk Hong; Zoghbi, Marianne; Lazcano, Rossana; Ingram, Davis; Wani, Khalida; Keung, Emily Z.; Zarzour, M. Alejandra; Scally, Christopher P.; Hunt, Kelly K.; Conley, Anthony; Bishop, Andrew J.; et al. (Frontiers in Immunology, 2025)
BackgroundDedifferentiated liposarcoma (DDLPS) is one of the most common types of soft tissue sarcoma (STS) characterized by liposarcomatous differentiation and a predilection for the retroperitoneum. Despite the growing number of histology-specific immune checkpoint blockade (ICB) trials in STS, it is still difficult to identify the radiographic objective response rate (ORR) for DDLPS in the real world setting. This study aimed to evaluate the ORR and survival of patients with DDLPS treated with ICB at a single center.MethodsWe conducted a retrospective study of 31 patients with pathologically confirmed DDLPS treated with ICB at MD Anderson Cancer Center between 2018 and 2023. Patient demographics, disease characteristics, treatment history, and response to ICB were analyzed. Immunohistochemical analysis was performed on tumor samples to assess immune-related markers.ResultsORR by RECIST 1.1 was 3.2% (n=1/31). Among all patients (n=31), 6% achieved partial radiographic response, while 39% had stable disease, and 55% showed progressive disease. Median progression-free survival (PFS) was 3.5 (95%CI:1.9, 4.7) months, and overall survival (OS) after ICB initiation was 19.7 (95%CI: 8.8, not reached) months. Patients without prior systemic therapy demonstrated better OS (p=0.004). Immunohistochemistry revealed no relationship between pre- or post-ICB expression of CD8, CD20, CD21 and PDL-1 and response.ConclusionWhile the response to ICB in DDLPS remains limited, specific immune markers may influence treatment outcomes. CD20/21 post-ICB appear more important for prognosis. Further research is warranted to identify predictive factors for ICB efficacy in DDLPS.